Predictors of In-Hospital Death After Aneurysmal Subarachnoid Hemorrhage: Analysis of a Nationwide Database (Swiss SOS [Swiss Study on Aneurysmal Subarachnoid Hemorrhage]). Issue 2 (February 2018) - Stienen, Martin Nikolaus; Germans, Menno; Burkhardt, Jan-Karl; Neidert, Marian C.; Fung, Christian; Bervini, David; Zumofen, Daniel; Roethlisberger, Michel; Marbacher, Serge; Maduri, Rodolfo; Robert, Thomas; Seule, Martin A.; et al.
Abstract : Background and Purpose—: To identify predictors of in-hospital mortality in patients with aneurysmal subarachnoid hemorrhage and to estimate their impact. Methods—: Retrospective analysis of prospective data from a nationwide multicenter registry on all aneurysmal subarachnoid hemorrhage cases admitted to a tertiary neurosurgical department in Switzerland (Swiss SOS [Swiss Study on Aneurysmal Subarachnoid Hemorrhage]; 2009–2015). Both clinical and radiological independent predictors of in-hospital mortality were identified, and their effect size was determined by calculating adjusted odds ratios (aORs) using multivariate logistic regression. Survival was displayed using Kaplan–Meier curves. Results—: Data of n=1866 aneurysmal subarachnoid hemorrhage patients in the Swiss SOS database were available. In-hospital mortality was 20% (n=373). In n=197 patients (10.6%), active treatment was discontinued after hospital admission (no aneurysm occlusion attempted), and this cohort was excluded from analysis of the main statistical model. In the remaining n=1669 patients, the rate of in-hospital mortality was 13.9% (n=232). Strong independent predictors of in-hospital mortality were rebleeding (aOR, 7.69; 95% confidence interval, 3.00–19.71; P <0.001), cerebral infarction attributable to delayed cerebral ischemia (aOR, 3.66; 95% confidence interval, 1.94–6.89; P <0.001), intraventricular hemorrhage (aOR, 2.65; 95% confidence interval, 1.38–5.09; P =0.003), and new infarction post-treatment (aOR, 2.57; 95% confidence interval, 1.43–4.62; P =0.002). Conclusions—: Several—and among them modifiable—factors seem to be associated with in-hospital mortality after aneurysmal subarachnoid hemorrhage. Our data suggest that strategies aiming to reduce the risk of rebleeding are most promising in patients where active treatment is initially pursued. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT03245866. Abstract : Supplemental Digital Content is available in the text.